Evaluation of Amyloid β42 Aggregation Inhibitory Activity of Commercial Dressings by A Microliter-Scale High-Throughput Screening System Using Quantum-Dot Nanoprobes - Masahiro Kuragano; Wataru Yoshinari; Xuguang Lin; Keiya Shimamori; Koji Uwai; Kiyotaka Tokuraku (Foods, 2020)
The aggregation and accumulation of amyloid β (Aβ) in the brain is a trigger of pathogenesis for Alzheimer’s disease. Previously, we developed a microliter-scale high-throughput screening (MSHTS) system for Aβ42 aggregation inhibitors using quantum-dot nanoprobes. The MSHTS system is seldom influenced by contaminants in samples and is able to directly evaluate Aβ42 aggregation inhibitory activity of samples containing various compounds. In this study, to elucidate whether the MSHTS system could be applied to the evaluation of processed foods, we examined Aβ42 aggregation inhibitory activity of salad dressings, including soy sauces. We estimated the 50% effective concentration (EC50) from serial diluted dressings. Interestingly, all 19 commercial dressings tested showed Aβ42 aggregation inhibitory activity. It was suggested that EC50 differed by as much as 100 times between the dressings with the most (0.065 ± 0.020 v/v%) and least (6.737 ± 5.054 v/v%) inhibitory activity. The highest activity sample is traditional Japanese dressing, soy sauce. It is known that soy sauce is roughly classified into a heat-treated variety and a non-heat-treated variety. We demonstrated that non-heat-treated raw soy sauce exhibited higher Aβ42 aggregation inhibitory activity than heat-treated soy sauce. Herein, we propose that MSHTS system can be applied to processed foods.